2017
DOI: 10.1002/anie.201705339
|View full text |Cite
|
Sign up to set email alerts
|

Strand Displacement in Coiled‐Coil Structures: Controlled Induction and Reversal of Proximity

Abstract: Coiled-coil peptides are frequently used to create new function upon the self-assembly of supramolecular complexes. A multitude of coil peptide sequences provides control over the specificity and stability of coiled-coil complexes. However, comparably little attention has been paid to the development of methods that allow the reversal of complex formation under non-denaturing conditions. Herein, we present a reversible two-state switching system. The process involves two peptide molecules for the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…energy transfer dyes, nanoparticles, drugs) in close proximity, or with a higher density, than modifying origami staple strands alone. Several reports have showed that coil assembly can be controlled with light using azobenzenes, 30 or that coils can be displaced similar to DNA 8,9 by introducing an unpaired partial heptad "toehold"; 31 both of these mechanisms can in principle now be used to dynamically control DNA structure selfassembly. Finally, we note that coiled-coil DNA conjugates will enable integration of recombinant proteins through genetic fusion of one of the two peptide partners, and may enhance the stability of hybrid nanomaterials by not requiring supraphysiological counterion concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…energy transfer dyes, nanoparticles, drugs) in close proximity, or with a higher density, than modifying origami staple strands alone. Several reports have showed that coil assembly can be controlled with light using azobenzenes, 30 or that coils can be displaced similar to DNA 8,9 by introducing an unpaired partial heptad "toehold"; 31 both of these mechanisms can in principle now be used to dynamically control DNA structure selfassembly. Finally, we note that coiled-coil DNA conjugates will enable integration of recombinant proteins through genetic fusion of one of the two peptide partners, and may enhance the stability of hybrid nanomaterials by not requiring supraphysiological counterion concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…1 Eklund et al started with the E 3 /K 3 coiled coil pair of 21 amino acid (aa) peptides, where each E unit is a negatively charged 7 aa "heptad repeat" and each K unit is a positively charged 7 aa "heptad repeat" peptide. [26][27][28] Keeping the length of the negatively charged peptide constant, Eklund et al explored the effect of decreasing the length of the K peptide on coiled coil stability. They chose to work with K peptides of 18 or 19 aa, which interact with the E peptide with dissociation constants of 1.7 μM and 81 nM, respectively.…”
Section: Protein-based Paint Methodsmentioning
confidence: 99%
“…Hitherto, CC assemblies responsive to pH, metal ions, light, redox conditions, hydrophobic ligands or phosphorylation have been successfully designed. Additionally, CC strand displacement using peptides with different affinities to guide the exchange of CC assemblies has recently been presented . Metal ions are particularly suitable for controlling conformational changes due to their ubiquitous role in various biological systems .…”
Section: Methodsmentioning
confidence: 99%